Formal Language Use in Conversations among Second-Semester Students at English Education Study Program of Universitas Nias - Riswan Zega; Robin Motani Daeli; Etikat Muliana Zebua; Yarlin Harefa; Fister Handayanti Zai; Meiwan Tuti Eka J. Zendrato; Juni Hati K. Hulu (JELITA, 2024)
This study aims to describe the use of formal language in conversations among college students semester II at English education study program of Universitas Nias. This research used comprehensive qualitative method. Data were taken from video conversations to evaluate how students apply formal language in formal situations. The results show that students begin to use formal language with respect and professionalism through the use of standard vocabulary, complex sentence structures, and correct grammar. The study also highlights the factors that influence the use of formal language, as well as the importance of practice and feedback in developing formal speaking skills and preparing students for future professional environments. By emphasizing formal language practice and providing constructive feedback, teaching can help students build competence and confidence in a variety of communication contexts.